MENDALAMI LIVING QUR'AN: ANALISIS PENDIDIKAN DALAM MEMAHAMI DAN MENGHIDUPKAN AL-QUR'AN: EXPLORING THE LIVING QUR'AN: AN ANALYSIS OF EDUCATION IN UNDERSTANDING AND LIVING THE QUR'AN. - Murtadlo, Ghulam; Khotimah, Anggrayny Khusnul; Alawiyah, Dina; elviana, elza; Nugroho, Yanwar Cahyo; Ayuni, Zulfi (CV. Kalimasada Group, 2023)
The idea of a living Qur'an and the role of education in understanding and bringing the Qur'an to life are the subjects of this study. The study of the Qur'an includes more than textual interpretation and analysis; it also includes social phenomena related to the day-to-day presence of the Qur'an, or